Instrumenty finansowego wsparcia i ich wpływ na konkurencyjność gospodarstw rolnych - Przygodzka, Renata (Financial Support Instruments and Their Influence on Farms Competitiveness, 2006)
The agriculture and farms competitiveness depends on many different factors. The macroeconomical and agricultural policy are universally recognized as the most important. In the transformation period the agricultural policy was insignificantly eliminating negative effects of the macroeconomical policy influence on the competitiveness of Polish farms. At present, owing to the Common Agricultural Policy (CAP) instruments, there are chances to make it more significant. However, it is to remember, that not all instruments contribute to it equally.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 2, s. 261-266